2020
DOI: 10.1177/0145445520925429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Free-operant Preference Assessment: Outcomes of Varying Session Duration and Problem Behavior

Abstract: Previous researchers have found brief versions of preference assessments correspond to outcomes of longer preference assessments, and that varying levels of problem behavior occur in different preference assessments. Researchers conducted two studies to examine 1-, 2-, and 5-min duration outcomes of the free-operant preference assessment and evaluated the correspondence between the shorter and longer session durations and to identify frequency of problem behavior at each duration. Researchers also assessed rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Students roam freely throughout the room as a member from the educational team measures the duration of student’s engagement with various objects or activities across the assessment period. Assessment periods can be up to 30 min (Rapp et al, 2010); however, research has demonstrated that abbreviated session durations (e.g., 1–5 min) may still successfully identify preferred items that will function as effective reinforcers (Clay et al, 2020). At the end of the session period, the educational team determines the hierarchy of preferred objects or activities by calculating the percentage of session engagement with each item and ranking the items based on highest to lowest percent of engagement (Roane et al, 1998).…”
Section: Preference Assessmentsmentioning
confidence: 99%
“…Students roam freely throughout the room as a member from the educational team measures the duration of student’s engagement with various objects or activities across the assessment period. Assessment periods can be up to 30 min (Rapp et al, 2010); however, research has demonstrated that abbreviated session durations (e.g., 1–5 min) may still successfully identify preferred items that will function as effective reinforcers (Clay et al, 2020). At the end of the session period, the educational team determines the hierarchy of preferred objects or activities by calculating the percentage of session engagement with each item and ranking the items based on highest to lowest percent of engagement (Roane et al, 1998).…”
Section: Preference Assessmentsmentioning
confidence: 99%